The hope of glory : education and exhortation in the Epistle to the Colossians - Wilson, Walter T. (Novum Testamentum, Supplements, 1997)
This study explores the background, character, and function of Colossians as a form of theological education and appeal in the Pauline tradition. A historical, literary, rhetorical, and narrative analysis of the text shows how its theological affirmations and claims were presented so as to engage the life of its readers in practical ways and in practical contexts, especially in order to direct their moral formation as Christians and their self-understanding as a Christian community in a time of controversy. The specific strategies adopted by the author in designing his message and instructing the readers are familiar from Hellenistic conventions of moral and spiritual guidance, particularly those conventions associated with philosophic paraenesis , or moral exhortation for recent converts.